Animal Symbology in Art, from Antiquity to the Middle Ages, Contrasted with the Christian Literature of the 2nd Century and the First Half of the 3rd Century - Navascués Alcay, Santiago (Eikón / Imago, 2024)
Since Late Antiquity times, there has been an intense Christianization of pagan myths and beliefs about fauna, both in textual production and in art. This article intends to clarify how that process came to be. After the analysis of pagan sources, both literary and archaeological, and of Christian literature of the second century and the first half of the third century, the study concludes that early Christians have their own animal symbology, different from their pagan neighbors, and are not interested in carrying out any Christian assimilation of pagan representations and stories of animals. This Christianization will take place in subsequent years and will occur in parallel in art and literature.